Improved anaerobic digestion efficiency of high-solid sewage sludge by enhanced direct interspecies electron transfer with activated carbon mediator. (October 2020) - Sun, Wen-Xin; Fu, Shan-Fei; Zhu, Rong; Wang, Zhen-Yu; Zou, Hua; Zheng, Yi
Highlights: AC addition improved the efficiency of high-solid AD. AC dosage in the range of 2–12 g/L has little effect on AD performance. Enhanced DIET by AC resulted in higher AD efficiency. The redox activity of AC might play an important role in promoting DIET. Abstract: High-solid anaerobic digestion (AD) faces the problems of easy acidification and low methane production efficiency. In this study, activated carbon (AC)-enhanced direct interspecies electron transfer (DIET) was investigated to overcome such problems. Results showed the conversion of volatile fatty acids (VFAs) into methane rate was increased with AC addition, which led improved methane production efficiency. The methane yields from the early AD stage improved by 124.0–146.3% with AC addition. The T80 shortened by 8–9 days with AC addition. The relative abundances of Geobacter, Syntrophomonas and Methanosaeta that associated with DIET improved for 63.65%, 256.3% and 4.35% by AC addition, which reflected the enhanced DIET with AC addition. The redox activity of AC might be responsible for the enhanced DIET. This study would advance the understanding of DIET and provide a potential solution to the problems existed in high-solid AD.